Post COVID-19 among young adults– prevalence and associations with general health, stress, and lifestyle factors - Sandra Ekström; Ida Mogensen; Maria Ödling; Antonios Georgelis; Anne-Sophie Merritt; Sophia Björkander; Erik Melén; Anna Bergström; Inger Kull (BMC Public Health)
Abstract Background The prevalence of post COVID-19 condition (PCC) after mild infection among young adults is largely unknown, as are its impact on health and lifestyle factors. Objective To assess the prevalence of PCC among young adults and its impact on general health, stress, and changes in lifestyle factors three years after the onset of the pandemic. Methods The study population (n = 2,098) included participants from the population-based cohort BAMSE (aged 27–30 years). PCC symptoms and changes in lifestyle factors during the pandemic were assessed in a questionnaire distributed in September–December 2023 and analyzed cross-sectionally. Stress, physical activity, and general health were also assessed pre-pandemic (2016–2019) and analyzed longitudinally. PCC was defined as ≥ 1 symptom lasting for ≥ 2 months after COVID-19. Results In total, 1,577 (75.5%) reported previous COVID-19. Among these, 166 (10.5%) reported previous and 62 (3.9%) ongoing PCC. The most common ongoing symptoms were altered smell/taste, psychological symptoms, and fatigue. Both pre- and post-pandemic general health differed significantly in relation to PCC in cross-sectional analyzes (all p < 0.05), with the lowest health reported by those with ongoing PCC. Participants with ongoing PCC also had a reduction in well-being in longitudinal analyses (p = 0.04). This group also reported more adverse changes in lifestyle factors and health during the pandemic such as reduced physical activity (p < 0.001) and worsened dietary habits (p = 0.03). However, there was no significant difference in the longitudinally measured perceived stress scale among individuals with PCC. Conclusions Almost 4% of young adults with previous self-reported COVID-19 had ongoing symptoms of PCC three years after the onset of the pandemic. This group reported poorer health and more adverse changes in lifestyle factors than participants without PCC. Targeted healthcare interventions for young adults with PCC are warranted.